On Theriac to Piso, attributed to Galen : a critical edition with translation and commentary - Leigh, Robert, 1961- (Studies in Ancient Medicine, 2016)
Robert Leigh offers a critical edition with translation into English, commentary and introduction of the pharmacological treatise On Theriac to Piso traditionally attributed to Galen. The focus of the work is on the question of authorship and Leigh seeks to show on textual, pharmacological, doctrinal and historical grounds that the attribution to Galen is at least highly problematic and probably mistaken. As well as marshalling the arguments in the introduction, Leigh seeks in the commentary not only to give a general exegesis of the text but also to identify points of agreement and points of difference between the treatise and other works which are undisputedly in the genuine Galenic corpus.